Flameless combustion of propane-air mixture in a laboratory scale burner - Abuelnuor, A. A. A. (2014)
In this work, the operational and emission of the laboratory scale burner under the flameless combustion regime using propane is examined. The combustor is equipped with parallel jet burner systems with controlled gas fuel and oxidizer. The combustor consists of several ports that are used to measure temperature variation and analyze gas emission. The atmospheric air was heated by flowing it inside the chamber until the air temperature increased to approximately the auto ignition temperature of the fuel. The furnace under investigation has successfully produced temperature uniformity ratios that are one order of magnitude less than such of the visible flame mode. It is observed that, flameless combustion can be achieved by using propane as a fuel. The value of NOX emission during flameless combustion was reduced of about 70% in average compared to the conventional flame at certain range of equivalence ratio.